2020
DOI: 10.1101/2020.09.21.20199018
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epidemiology of COVID-19 vs. Influenza: Differential Failure of COVID-19 Mitigation among Hispanics

Abstract: BACKGROUND: During the early phases of the COVID-19 pandemic, predominantly African-American or Hispanic communities were disproportionately impacted. We sought to better understand the epidemiology of COVID-19 among hospitalized Hispanic patients by comparing individual and census-tract level characteristics of patients diagnosed with COVID-19 to those diagnosed with influenza, another viral infection with respiratory transmission. We evaluated the temporal changes in epidemiology across race-ethnicity rela… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Direct comparison between these studies and Table 4 Comparing trends during a concentrated flu season (October to March) with the full year in 2016 and 2017 in order to rule out the effect of non-influenza-related pneumonia, New York City ours is difficult because most are limited to data early in the pandemic, include different baseline influenza years, and utilize populations with different socioeconomic variation than ours. For example, two studies (from the Veterans Health Administration and Cook County, Illinois) reported even greater racial/ethnic disparities during COVID-19, with higher rates of COVID-19 hospitalizations among Black and Hispanic populations compared with previous influenza seasons [19,21]. This difference may be related to the fact that our sample is relatively homogenous economically compared to other samples.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Direct comparison between these studies and Table 4 Comparing trends during a concentrated flu season (October to March) with the full year in 2016 and 2017 in order to rule out the effect of non-influenza-related pneumonia, New York City ours is difficult because most are limited to data early in the pandemic, include different baseline influenza years, and utilize populations with different socioeconomic variation than ours. For example, two studies (from the Veterans Health Administration and Cook County, Illinois) reported even greater racial/ethnic disparities during COVID-19, with higher rates of COVID-19 hospitalizations among Black and Hispanic populations compared with previous influenza seasons [19,21]. This difference may be related to the fact that our sample is relatively homogenous economically compared to other samples.…”
Section: Discussionmentioning
confidence: 81%
“…While many studies have documented the racial/ethnic disparities in COVID-19 hospitalizations [14], only a handful have directly compared COVID-19 with historical influenza patterns. These studies have largely focused on the clinical complications and outcomes among those hospitalized [15][16][17], though some include patient characteristics as part of their descriptive analysis [18][19][20] or as part of a focused analysis among one ethnic group [21]. Direct comparison between these studies and Table 4 Comparing trends during a concentrated flu season (October to March) with the full year in 2016 and 2017 in order to rule out the effect of non-influenza-related pneumonia, New York City ours is difficult because most are limited to data early in the pandemic, include different baseline influenza years, and utilize populations with different socioeconomic variation than ours.…”
Section: Discussionmentioning
confidence: 99%